Srovnání lidského choriového gonadotropinu (Pregnyl 10 000 IU i.m.) s GnRH agonistou (triptorelin 0.2 mg s.c.) pro maturaci oocytů u stejných dárkyn vajícek--klinické a embryologické charakteristiky - Streda, R; Mardesic, T; Sobotka, V; Koryntová, D; Hybnerová, L; Jindra, M; Paseková, V; Slámová, J; Stevíková, M; Voboril, J; Jelínková, L; Vilímová, S; et al. (Ceska gynekologie, 2011)
OBJECTIVE: To compare clinical and embryological characteristics in donor cycles triggered for final oocytes maturation with Pregnyl 10 000 IU i.m. versus triptorelin 0.2 mg s.c. in the same patients in two sequential stimulation cycles. The aim of the study is to decrease the risk of the development of ovarian hyperstimulation syndrome (OHSS) at high response donors by the replacement of Pregnyl 10 000 IU i.m. vs. triptorelin 0.2 mg s.c. The administration of a single dose of gonadotropin-releasing hormone agonist (triptorelin 0.2 mg s.c.) induces release of LH from the pituitary gland similarly to a spontaneous LH surge. SUBJECT: Prospective cross-over trial. SETTING: Sanatorium Pronatal, Praha. SUBJECT AND METHOD: From August 2009 to July 2010 we analysed 24 stimulation cycles in 12 egg donors treated with GnRH antagonist protocol with recombinant FSH (follitropin beta). We identified patients with more than 15 follicles during examination by transvaginal ultrasound. When at least 3 leading follicles reached 17 mm in diameter we administrated Pregnyl 10 000 IU i.m. for final oocytes maturation and triptorelin 0.2 mg s.c in the subsequent treatment cycle. RESULTS: The primary outcome measure was number of oocytes, proportion mature oocytes and fertilized oocytes. The secondary outcome were duration of FSH stimulation, total dose of gonadotropins and mean daily dose of gonadotropins. Data was analysed by paired t-test. We retrieved 17.2 +/- 8.6 vs. 15.8 +/- 5.3 (ns) oocytes, 12.6 +/- 7.3 vs. 13.0 +/- 5.4 (ns) metaphase II oocytes, proportion of metaphase II oocytes (%) was 73 vs. 83 (ns), number of fertilized oocytes 11.5 +/- 6.7 vs. 11.7 +/- 4.5 (ns), fertilization rate (%) 91 vs. 90 (ns) in Pregnyl's vs. triptorelin's group, resp. Duration of FSH stimulation (days) 12.2 +/- 0.8 vs. 12.4 +/- 0.7 (ns), total dose of gonadotropins (IU) 1744 +/- 277 vs. 1740 +/- 276 (ns), mean daily dose of gonadotropins (IU) 238 +/- 43 vs. 221 +/- 36 (ns), were not statistically different in both groups. CONCLUSIONS: Number of mature oocytes and subsequent embryonic cleavage is comparable to standard hCG treatment. There are no differences in clinical and embryological characteristics in both groups. Only one patient with administration of Pregnyl 10 000 IU i.m. was treated for OHSS grade II by vaginal paracentesis. Administration of triptorelin 0.2 mg s.c. is a safe and effective approach to achieve mature oocytes in egg donation programme, where we do not take care of implantation, which has got some limitations based on several studies.
Keywords: Oocyte Donation; oocyty; lidé; choriogonadotropin; Oocytes; Chorionic Gonadotropin; ženské pohlaví; darování oocytu; Humans; ovariální hyperstimulační syndrom; Ovarian Hyperstimulation Syndrome; Female; Triptorelin Pamoate; triptorelin-pamoát